Carbon/hemp bio-hybrid composites: Effects of the stacking sequence on flexural, damping and impact properties. (15th June 2020) - Pinto, Fulvio; Boccarusso, Luca; De Fazio, Dario; Cuomo, Stefano; Durante, Massimo; Meo, Michele
Abstract: This work is focused on the design and production of hybrid laminates in which the reinforcement is a combination of carbon and hemp fibres. Four different stacking sequences were considered and pure hemp and pure carbon laminates were fabricated as references. Three-point bending, interlaminar shear, damping and impact tests at different energy levels in the range of 5–20 J were carried out to understand how the presence and the position of hemp fabrics affects the mechanical response. It was pointed out that it is possible, for example, to tune the flexural modulus, the absorbed energy and the damage extension after impact very close to the one of pure carbon, by placing the hemp layers close to the neutral axis. Otherwise, to improve the absorbed energy in both flexural and impact dynamic conditions, the best result was achieved when the hemp layers are placed on the laminate top side.